2007
DOI: 10.1093/hmg/ddm287
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine tract length of human androgen receptors affects hormone-dependent and -independent prostate cancer in mice

Abstract: The androgen receptor (AR) is involved in the initiation and progression of prostate cancer and its transition to androgen independence. Genetic variation in AR may contribute to disease risk and has been studied for a polymorphic N-terminal glutamine (Q) tract that shows population heterogeneity. While the length of this tract is known to affect AR in vitro, association with disease is complicated by genetic and environmental factors that have led to discordant epidemiological findings. To clarify the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Q-tract length inversely correlates with AR transcriptional activity in vitro , seen as altered prostatic gene expression and endpoints of androgen action such as seminal vesicle weight [4, 17, 65]. Previously, we showed that AR Q-tract length modifies PCa onset, progression and treatment response in the aggressive TRAMP mouse model [3]. Thus, variable AR transcriptional activity has the potential to modulate the effect of additional oncogenic events and alter the course of disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Q-tract length inversely correlates with AR transcriptional activity in vitro , seen as altered prostatic gene expression and endpoints of androgen action such as seminal vesicle weight [4, 17, 65]. Previously, we showed that AR Q-tract length modifies PCa onset, progression and treatment response in the aggressive TRAMP mouse model [3]. Thus, variable AR transcriptional activity has the potential to modulate the effect of additional oncogenic events and alter the course of disease.…”
Section: Resultsmentioning
confidence: 99%
“…The antibodies used in this study included AR N-20 (Santa Cruz # sc-816, 1:500 dilution), phospho-AKT (Ser473) (Cell Signaling #9271, 1:100 dilution), and PTEN (Cell Signaling #9188, 1:80 dilution). Immunohistochemistry (IHC) was performed essentially as described for AR and pAKT [3], and for PTEN [61, 13]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AR Q tract influence noted in mouse PCa (4) suggests differences in AR strength may contribute to differences in response to androgen ablation. Greater transcriptional activity of short Q tract ARs is due to greater interaction between AR's N and C terminus (N/C interaction), which leads to greater response at lower ligand levels and greater coactivator recruitment (9).…”
Section: Task 2 Determine the Role Of The Q Tract In Ligand-independmentioning
confidence: 99%
“…Upon activation of a prostate-targeted oncogene however distinct allele-dependent differences in disease progression are evident. These allelic differences also impact progression following androgen ablation (4). Mice with the more active AR12Q respond well to castration, whereas those with the weaker AR48Q show no benefit from treatment.…”
Section: Introductionmentioning
confidence: 99%